Mapping of traditional healthcare providers and their healing approaches in a tribal community of district Sirohi, Rajasthan - Rakhi Dwivedi; Prachi Goyal; Suraj S. Yadav; Pradeep Dwivedi; Pratibha Singh; Kuldeep Singh (Journal of Family Medicine and Primary Care)
Introduction: Traditional applications of medicinal plants in healthcare practices provide indication to new therapeutic concepts; hence, their relevance is highly recognized. The objective of the study was to map the traditional healers from the aspirational district and scientific documentation of their healing practices to treat various diseases. Method: This was community-based study in tribal subpopulation zone of district Sirohi. The data was collected through field survey and interviews of tribal healers by using semi-structured questionnaire. Result: We identified 1015 tribal healers (68% male and 32% female), and all belong to Bhil, Meena, and Garasia communities of district Sirohi. The mean age was 60.45 ± 16.56 years, 82.6% healers were uneducated, and 12.6% had primary education, while 1.2% were graduates. Tribal healers act as primary point of care for tribal community and practiced various treatment modalities including herbal healing (32.7%), diviners (28.9%), child birth attendant (24.7%), and bone setters (13.7%). We recorded 88 herbal healing practices from tribal communities of district Sirohi and scientifically documented. The common diseases treated by tribal healers included wound healing, skin infection, fever, arthritis, pain, diarrhea, cough, and cold. The Fabaceae family was credited with highest number (17%) of plants used by herbal healers. It was also noted that some of the plants used for medicinal purpose are endangered and overexhausted. Conclusion: Ethnopharmacological data is the foundation for further validation and value addition of herbal healthcare practices. The mapping of indigenous knowledge holders and scientific documentation of their knowledge might be a crucial step for providing clue regarding new therapeutic molecules.